2012
DOI: 10.1007/s00432-011-1138-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of tumor suppressor TSLC1 by a survivin-regulated oncolytic adenovirus significantly inhibits hepatocellular carcinoma growth

Abstract: These data suggest that an oncolytic adenovirus expressing TSLC1 is effective and support that SD55-TSLC1 may be a potent antitumoral agent for future clinical trials of liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Our study is the first to report miR-1246 could regulate invasion and migration of HCC cell via targeting CADM1. There is no doubt that CADM1 functions as a tumor suppressor gene in HCC [23, 28]. In this study, we also demonstrated that CADM1 RNA interference results in up-regulation of invasion and migration in HCC cell lines.…”
Section: Discussionsupporting
confidence: 70%
“…Our study is the first to report miR-1246 could regulate invasion and migration of HCC cell via targeting CADM1. There is no doubt that CADM1 functions as a tumor suppressor gene in HCC [23, 28]. In this study, we also demonstrated that CADM1 RNA interference results in up-regulation of invasion and migration in HCC cell lines.…”
Section: Discussionsupporting
confidence: 70%
“…Tsujiuchi et al reported that in HCC induced by N-nitrosodiethylamine, the 5’ upstream region of TSLC1 was methylated and its expression was reduced [18]. Additionally, some researchers reported that restoration of TSLC1 could effectively inhibit HCC growth [28]. In the present study, we were the first to identify TSLC1 as a direct target of miRNA-873 in HCC cells.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, TSLC1 mediates potential anti-cancer effects. Notably, our previous study reported that OA encoding TSLC1 exhibits significant antitumor effects on hepatocellular cancer cells [25] . The differences between these studies include the OA design and the cancer types investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Of significance, survivin has aberrantly high expression in cancer cells such as lung cancer but little expression in most normal tissues, making survivin an attractive anticancer target [22,23] . Recent studies have shown that a designed oncolytic adenovirus driven by the survivin promoter exhibited a tumor-selective antitumor effect in vitro and in vivo [3,24,25] , suggesting that the survivin promoter is a good candidate for cancer therapy. To improve the OA tumor-specificity, a 24 bp region within the E1A conserved region 2 (CR2), which is responsible for binding the retinoblastoma (Rb) protein, was deleted.…”
mentioning
confidence: 99%